ANALISIS PRODUK DOMESTIK REGIONAL BRUTO SEKTOR PERTANIAN DAN HUBUNGANNYA DENGAN KESEMPATAN KERJA SERTA DISTRIBUSI PENDAPATAN DI PROVINSI SUMATERA SELATAN - Erlina Rufaidah; Dwi Wulan Sari (Faculty of Teacher Training and Education, University of Lampung, 2013)
The purposes from this research are 1) For analysis gross domestic regional product (GDRP) with work opportunity in South Sumatera Province, 2) For analysis the influence from output ratio in agriculture sector with earning distribution in South Sumatera Province. The method in this research is history study. The data are collected in a kind of secondary data that are collected in the time series type in 21 years, since from 1985 until 2005. The influence from GRDP in crop of food and horticulture, plantation, forestry, fishery sub-sector have really significant with work opportunity in agriculture sector in South Sumatera Province. The value of Gini Ratio are about 0,25 – 0,30 which is means earning Iameness still in safe boundary. The capital ratio value influences are significant in level test 30 percent with earning distribution.Keywords : GDRP, learning distribution, work opportunity